Anxiety experienced in high-risk pregnancy - Inga Janik; Martyna Maciejewska; Anna Fabian-Danielewska; Katarzyna Korabiusz; Agata Wawryków; Agnieszka Wilczyńska; Monika Stecko (Kazimierz Wielki University, 2018)
Pregnancy is the time of new experiences. A woman is preparing for significant changes that will strengthen the process of maternity. It's the moment of numerous changes both physiological and emotional.A pregnant woman is experiencing various emotions, such as hope and happiness but also anxiety and concern. In a natural way she starts to change her goals and plans, she imagines her future. However, on each stage of pregnancy there can occur numerous complications related to various factors, for example: infant diseases, injuries, mother illnesses. Different factors can cause the incorrect course of pregnancy. Situation like this often causes difficult feelings in women, especially strong anxiety. Numerous researchers emphasize different social-economic situation of women with possible high-risk pregnancy than women with normal pregnancy because the process of preparing to labor is interrupted. Women often need medical treatment, hospitalization, their physical activity is changed as it is often advised to lie down for long periods of time. This strengthens a woman fears and anxiety for child's health and life